2014
DOI: 10.1364/oe.22.011592
|View full text |Cite
|
Sign up to set email alerts
|

Passive intrinsic-linewidth narrowing of ultraviolet extended-cavity diode laser by weak optical feedback

Abstract: We present a simple method for narrowing the intrinsic Lorentzian linewidth of a commercial ultraviolet grating extended-cavity diode laser (TOPTICA DL Pro) using weak optical feedback from a long external cavity. We achieve a suppression in frequency noise spectral density of 20 dB measured at frequencies around 1 MHz, corresponding to the narrowing of the intrinsic Lorentzian linewidth from 200 kHz to 2 kHz. Provided additional active low-frequency noise suppression and long-term drift compensation, the syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…When the locking is fully engaged, including the fast feedback path, the laser stayed locked despite repeated impacts of the hammer on the table, briefly jumping in frequency before returning to its locked point. This is in contrast to earlier, piezoelectricstabilized designs [9,10], where even loud conversation or hand-clapping can cause the laser to fall out of lock.…”
Section: Laser Noise Measurementcontrasting
confidence: 61%
See 1 more Smart Citation
“…When the locking is fully engaged, including the fast feedback path, the laser stayed locked despite repeated impacts of the hammer on the table, briefly jumping in frequency before returning to its locked point. This is in contrast to earlier, piezoelectricstabilized designs [9,10], where even loud conversation or hand-clapping can cause the laser to fall out of lock.…”
Section: Laser Noise Measurementcontrasting
confidence: 61%
“…Such an external cavity increases the optical quality factor Q due to greater cavity length or finesse compared to an integrated cavity [7]. Optical feedback from an external fiber [8] has contributed to sub-kilohertz linewidth narrowing in DBR lasers [9] and traditional ECDLs [10] by adding a ∼ 1 m long external cavity to the laser.…”
Section: Introductionmentioning
confidence: 99%
“…Savchenkov et al [22] have reported a similar value (≈ 30 kHz) for self-injection locked LD at 370 nm. ECDL frequency stabilizations based on external cavity optical feedback [8,23] allow to narrow the linewidth down to few kHz but the large external cavity (meter long) and moving parts limit the observation time from minutes to seconds. To reach stable SF operation, a careful consideration should be given to the setup.…”
Section: Arxiv:210204129v1 [Physicsoptics] 8 Feb 2021mentioning
confidence: 99%
“…There are different noise sources, which can affect on the laser's linewidth: (1) fundamental noises (white, shot, and thermal noises): the intrinsic Lorentzian linewidth can be reduced using optical feedback 44 and (2) flicker (1∕f) noises and technical noises (noises from the laser driver, piezo drift, mechanical vibrations, temperature fluctuations, acoustic noises, air pressure fluctuations). These noise sources broaden the laser linewidth.…”
Section: Frequency Stabilizationmentioning
confidence: 99%